Endodontic management of central incisor associated with large periapical lesion and fused supernumerary root: a conservative approach - Gautam P. Badole; Pratima R. Shenoi; Ameya Parlikar (Restorative Dentistry & Endodontics)
Fusion and gemination are developmental anomalies of teeth that may require endodontic treatment. Fusion may cause various clinical problems related to esthetics, tooth spacing, and other periodontal complications. Additional diagnostic tools are required for the diagnosis and the treatment planning of fused tooth. The present case report describes a case of unilateral fusion of a supernumerary root to an upper permanent central incisor with large periapical lesion in which a conservative approach was used without extraction of supernumerary tooth and obturated with mineral trioxide aggregate to reach a favorable outcome.